Practices, Perceptions, and Attitudes in the Evaluation of Critically Ill Children for Bacteremia: A National Survey*. Issue 1 (January 2020) - Woods-Hill, Charlotte Z.; Koontz, Danielle W.; King, Anne F.; Voskertchian, Annie; Colantuoni, Elizabeth A.; Miller, Marlene R.; Fackler, James C.; Bonafide, Christopher P.; Milstone, Aaron M.; Xie, Anping
Abstract : Objectives: Sending blood cultures in children at low risk of bacteremia can contribute to a cascade of unnecessary antibiotic exposure, adverse effects, and increased costs. We aimed to describe practice variation, clinician beliefs, and attitudes about blood culture testing in critically ill children. Design: Cross-sectional electronic survey. Setting: Fifteen PICUs enrolled in the Blood Culture Improvement Guidelines and Diagnostic Stewardship for Antibiotic Reduction in Critically Ill Children collaborative, an investigation of blood culture use in critically ill children in the United States. Subjects: PICU clinicians (bedside nurses, resident physicians, fellow physicians, nurse practitioners, physician assistants, and attending physicians). Interventions: None. Measurement and Main Results: Survey items explored typical blood culture practices, attitudes and beliefs about cultures, and potential barriers to changing culture use in a PICU setting. Fifteen of 15 sites participated, with 347 total responses, 15–45 responses per site, and an overall median response rate of 57%. We summarized median proportions and interquartile ranges of respondents who reported certain practices or beliefs: 86% (73–91%) report that cultures are ordered reflexively; 71% (61–77%) do not examine patients before ordering cultures; 90% (86–94%) obtain cultures for any new fever in PICU patients; 33% (19–61%) do not obtain peripheral cultures when an indwelling catheter is in place; and 64% (36–81%) sample multiple (vs single) lumens of central venous catheters for new fever. When asked about barriers to reducing unnecessary cultures, 80% (73–90%) noted fear of missing sepsis. Certain practices (culture source and indication) varied by clinician type. Obtaining surveillance cultures and routinely culturing all possible sources (each lumen of indwelling catheters and peripheral specimens) are positively correlated with baseline blood culture rates. Conclusions: There is variation in blood culture practices in the PICU. Fear and reflexive habits are common drivers of cultures. These practices may contribute to over-testing for bacteremia. Further investigation of how to optimize blood culture use is warranted. Abstract : Supplemental Digital Content is available in the text.